IMPROVEMENT OF STUDENTS' SCIENCE PROCESS SKILLS IN SCAFFOLDING-BASED PROBLEM BASED LEARNING ON THE MATERIAL OF TRAVELLING WAVES AND STATIONARY WAVES - Zahra Nadifa Elahi; Saeful Karim; Duden Saepuzaman (Physics Education Study Program, Faculty of Education and Teacher Training, UNSIQ, 2025)
The following study aims to investigate the improvement of students' science process skills in problem-based learning based on scaffolding, especially in the material of traveling waves and stationary waves. Using a quantitative method, the study included 35 students in class XI IPA from a public high school in Sukabumi city, which was determined using purposive sampling. The data collection process used pretest and posttest administered through science process skill assessment instrument. The N-Gain test was used to analyze the data. The study showed that there was a significant difference between the pretest and posttest scores after treatment, indicating an increase in students' science process skills supported by the normalized N-Gain value which was included in the moderate category. The increase in science process skills for indicators of observing, communicating, and concluding is categorized as moderate. While the increase for indicators of classifying, measuring, and predicting is categorized as high.